Ultrasound evaluation of muscle and tendon (Health Renaissance, 2013)
Background: Ultrasound has been shown to be effective in the diagnosis of musculoskeletal pathology, and its use continues to increase. Objective: To evaluate the role of ultrasound in detection of pathology of muscle and tendon, where the facility of advanced imaging modality is not available. Methods: Ultrasound evaluation of muscle and tendon was done in referred 550 patients with clinical history of localized pain or trauma. A detailed clinical history was taken before sonography. The clinical findings and provisional diagnosis were recorded. A routine ultrasound examination included imaging of the affected muscle and tendon. The findings were compared with contralateral limb.Results: Ultrasound showed ailment in 130 patients and was useful to detect lateral epicondylitis in 37 patients, tenosynovitis in 26, tear of muscle or tendon in 23, cystic lesions in 9, abscess in 17, myocysticercosis in 4, radiolucent foreign bodies in 3, muscle hernia in 2 and intramuscular hemangioma in 9 patients. Conclusion: High resolution ultrasound is a rapid and inexpensive technique.It can be used as a first line imaging modality for the musculoskeletal pathology particularly in developing countries with limited imaging facilities. Health Renaissance, January-April 2013; Vol. 11 No.1; 54-61 DOI: http://dx.doi.org/10.3126/hren.v11i1.7603